Keragaan Usahatani dan Kinerja Agribisnis Jagung di Kabupaten Ciamis - Kurnia, Rian; Andrie, Benidzar M; Aziz, Saepul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Corn productivity in West Java continues to decline from year to year. This is inversely proportional to the need for corn which increases from year to year. This research aims to assess the performance of agribusiness subsystems in sustainable corn agribusiness in Ciamis Regency. The performance of corn agribusiness development is explained using descriptive analysis and processed by grouping using percentages and then given a narrative explanation to provide an empirical picture of the primary data collected from respondents. The performance status of maize agribusiness development is discussed using an agribusiness system approach consisting of production input subsystem, production/on-farm subsystem, handling and processing subsystem, marketing subsystem and supporting facilities subsystem. Based on the results of the analysis of the performance of the corn agribusiness system in Ciamis Regency, it is in the good category (more than 60 percent). So it can be said that corn farmers in Ciamis Regency have implemented the corn agribusiness system well. This means that with good agribusiness performance, the development of corn in Ciamis Regency has the potential to continue to be developed in order to achieve corn self-sufficiency as proclaimed by the government. Only the performance of the supporting subsystem is in the sufficient category (less than 60 percent). This is because there are still many farmers who have not benefited from climate mitigation policies and access to financial institutions. Agribusiness performance is closely related to productivity because it is an indicator in determining how efforts to achieve high productivity in a farming business. In connection with this matter, the effort to conduct an assessment of the performance of agribusiness in the development of farming is important.